Maintaining Local Languages Through Local Content Curriculum: Analysis of Contextual Approaches and Field Learning - Kambu, Yosep; W Afasedanya, Betarixs; Wanimbo, Wetius; R. Malangsena, Robert (Lembaga Penelitian dan Pendidikan Mandala, 2024)
It is not impossible that language undergoes changes over time. The existence of local languages among teenagers and young people is no longer a communicative language choice in the environment where they are. The purpose of this research is to elaborate on the role of education, especially local curriculum, in preserving the local language by involving contextual approaches and field learning to teach the local language in schools. This study applies qualitative description with a literature review approach. Data is obtained by collecting reference materials such as books, theses, and journals manually and online. Manual data collection is done at the library, while online data collection involves downloading e-books and scientific journals from the last 10 years. The data are analyzed using content analysis, which involves reviewing books, journals, and theses to answer formulated questions. The results of this study indicate that an effective method for implementing local language learning is a method with contextual approaches and field learning. The contextual method applies components of constructivism, questioning, exploration, modeling, and authentic assessment. Meanwhile, field learning brings students closer to the relevance of context in learning the local language